Organizational justice in human resource management - Tan, Fee Yean; Yusof, Ab. Aziz (2014)
Organisation justice is conceptualized as a multidimensional construct.Organizational justice can affect not only the long term viability of an organization but also to a large extent determine the economic well being of a nation and its competitiveness in the global front.It is therefore have a great impact to the organizations especially in term of relationship between employer and employee.Treating employees unfairly could create negative attitudes (e.g. unlikely to accept job order, poorer performance,intentionally breaking the rules and regulations, etc.) among employees toward the management of an organization. Hence, lot of studies were made in order to increase fairness in the workplace which is a key factor for manager in reaching organizational goals that led to the successful of a nation as a whole.